A design methodology for a self-oscillating electronic ballast - Amira, Mustapa (2012)
The lighting system provides many opportunities for cost-effective energy saving without any sacrifice. The system is now part of Energy Conservation program over the world and reduction of energy consumption by implementing energy conservation schemes is needed. Incandescent lamps convert just five per cent of energy into light and the remainder into heat where as fluorescent lamps turn 25 per cent of energy into light.This project present a design methodology for develop a self-oscillating electronic ballast (SOEB) with using the mathematical modelling of SOEB. This project performs three different method design of electronic ballast. First method was using the zener diode, second using two-stage electronic ballast and lastly used the single-stage electronic ballast. The comparisons and discussions are carried out for all circuits designed. The differentials are used to define a suitable design for self oscillating electronic ballast.